Visualizing Anishinaabe Ceramics: A Collaborative Approach to Digital Archaeology - Kiazyk, Hillary V (Scholarship@Western, 2021)
This thesis explores how collaboration can enrich and inform a digital-archaeological project and the process of braiding interests of archaeologists and Indigenous community partners. Research was conducted in partnership with the staff from the Ojibwe Cultural Foundation (OCF) on Manitoulin Island. We focused on the production of a digital model and 3D print of Anishinaabe ceramics from the Providence Bay archaeological site. The OCF wanted the material culture from Providence Bay accessible to community members as the ceramics themselves were too fragile for display or teaching without risking further damage. A 3D print of a Providence Bay vessel was produced using archaeological illustration methods in a 3D modelling program (Blender), creating a model of a pot informed by previous archaeology. This partnership also resulted in the development of a novel methodology (the OCF Aahnkesjihgeh Method). Our partnership highlights the ways in which collaboration can incorporate multiple perspectives in digital-archaeological research.